Treatment of complex regional pain syndrome in adults: A systematic review of randomized controlled trials published from June 2000 to February 2012. (5th October 2012) - Cossins, L.; Okell, R.W.; Cameron, H.; Simpson, B.; Poole, H.M.; Goebel, A.
Abstract Complex regional pain syndrome (CRPS) is a disabling pain condition with sensory, motor and autonomic manifestations. Uncertainty remains about how CRPS can be effectively managed. We conducted a systematic review of randomized controlled trials (RCTs) for treatment and prophylactic interventions for CRPS published during the period 2000–2012, building on previous work by another group reviewing the period 1966–2000. Bibliographic database searches identified 173 papers which were filtered by three reviewers. This process generated 29 trials suitable for further analysis, each of which was reviewed and scored by two independent reviewers for methodological quality using a 15‐item checklist. A number of novel and potentially effective treatments were investigated. Analysing the results from both review periods in combination, there was a steep rise in the number of published RCTs per review decade. There is evidence for the efficacy of 10 treatments (3× strong – bisphosphonates, repetitive transcranial magnetic stimulation and graded motor imagery, 1× moderate and 6× limited evidence), and against the efficacy of 15 treatments (1× strong, 1× moderate and ×13 limited). The heterogeneity of trialled interventions and the pilot nature of many trials militate against drawing clear conclusions about the clinical usefulness of most interventions. This and the observed phenomenon of excellent responses in CRPS subgroups would support the case for a network‐ and multi‐centre approach in the conduct of future clinical trials. Most published trials in CRPS are small with a short follow‐up period, although several novel interventions investigated from 2000 to 2012 appear promising.